Mednarodno razvojno sodelovanje in slovenska diplomacija - Bučar, Maja (Teorija in praksa, 2011)
International development co-operation is an important segment of the diplomatic activities of developed countries within the international community. Countries have specific strategic political, economic or other goals which they wish to implement by allocating (and tying) development aid. These interests need to be defined on a long-term basis as improved possibilities for co-operation in areas where, through development aid, a more stable political environment and sustainable economic development is being created. Slovenia lists co-operation with the Western Balkans as its foreign policy priority along with its development co-operation focus. Yet the article claims that the current implementation of development co-operation is insufficiently embedded in the achievement of long-term political and economic interests in this region.
Keywords: International cooperation; Mednarodno sodelovanje; Razvojna pomoč; Development aid; Foreign policy; Zunanja politika; Diplomacija; Diplomacy; Slovenia; Slovenija; Southeastern Europe; Jugovzhodna Evropa